2008
DOI: 10.1097/iae.0b013e3181884fd2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Endophthalmitis Related to Intravitreal Injection of Bevacizumab and Ranibizumab

Abstract: The rate of endophthalmitis associated with intravitreal bevacizumab and ranibizumab is low, with an incidence of approximately 1 in 4,500 injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 39 publications
4
127
0
5
Order By: Relevance
“…10,11 However, the reported rate in the recent studies tends to be lower than that in early trials. [10][11][12][13][14][15][16] The rate of endophthalmitis seems to be the same among different anti-VEGF agents, 12 different injection settings, 15 and different geographical locations. 17 Recent studies reported that endophthalmitis caused by Streptococcus species was significantly more frequent after intravitreal injection than after intraocular surgery.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 However, the reported rate in the recent studies tends to be lower than that in early trials. [10][11][12][13][14][15][16] The rate of endophthalmitis seems to be the same among different anti-VEGF agents, 12 different injection settings, 15 and different geographical locations. 17 Recent studies reported that endophthalmitis caused by Streptococcus species was significantly more frequent after intravitreal injection than after intraocular surgery.…”
Section: Methodsmentioning
confidence: 99%
“…This rate is comparable to or better than other studies of endophthalmitis following intravitreal therapy and cataract surgery. 15,17,18,21,32,33,[35][36][37] As with endophthalmitis following cataract surgery, vitreous sampling achieved a higher organism yield rate compared with aqueous sampling. 28,32,33 However, as aqueous sampling yielded an organism that was not identified by vitreous sampling in two cases, it may be optimal to perform both vitreous and aqueous sampling in the event of PIAE in order to maximise the chance of identifying a causative pathogen.…”
Section: Microbiologymentioning
confidence: 99%
“…16,17,22,41 More recently, larger studies have been published reporting risk factors for PIAE. Shah et al 42 reported a case control study of 23 cases of PIAE that did not find any of the variables they studied to be significant risk factors.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations